Whereabouts ebook A novel. - Lahiri, Jhumpa (2021)
NEW YORK TIMES BESTSELLER • A marvelous new novel from the Pulitzer Prize-winning author of The Lowland and Interpreter of Maladies about a woman questioning her place in the world, wavering between stasis and movement, between the need to belong and the refusal to form lasting ties. “Another masterstroke in a career already filled with them.” — O, the Oprah Magazine Exuberance and dread, attachment and estrangement: in this novel, Jhumpa Lahiri stretches her themes to the limit. In the arc of one year, an unnamed narrator in an unnamed city, in the middle of her life’s journey, realizes that she’s lost her way. The city she calls home acts as a companion and interlocutor: traversing the streets around her house, and in parks, piazzas, museums, stores, and coffee bars, she feels less alone. We follow her to the pool she frequents, and to the train station that leads to her mother, who is mired in her own solitude after her husband’s untimely death. Among those who appear on this woman’s path are colleagues with whom she feels ill at ease, casual acquaintances, and “him,” a shadow who both consoles and unsettles her. Until one day at the sea, both overwhelmed and replenished by the sun’s vital heat, her perspective will abruptly change.   This is the first novel Lahiri has written in Italian and translated into English. The reader will find the qualities that make Lahiri’s work so beloved: deep intelligence and feeling, richly textured physical and emotional landscapes, and a poetics of dislocation. But Whereabouts , brimming with the impulse to cross barriers, also signals a bold shift of style and sensibility. By grafting herself onto a new literary language, Lahiri has pushed herself to a new level of artistic achievement.